A translational study of circulating cell-free microRNA-1 in acute myocardial infarction - Cheng, Yunhui; Tan, Ning; Yang, Jian; Liu, Xiaojun; Cao, Xiaopei; He, Pengcheng; Dong, Xiaoli; Qin, Shanshan; Zhang, Chunxiang (Clinical science (1979), 2010)
miRNAs (microRNAs) participate in many diseases including cardiovascular disease. In contrast with our original hypothesis, miRNAs exist in circulating blood and are relatively stable due to binding with other materials. The aim of the present translational study is to establish a method of determining the absolute amount of an miRNA in blood and to determine the potential applications of circulating cell-free miR-1 (microRNA-1) in AMI (acute myocardial infarction). The results revealed that miR-1 is the most abundant miRNA in the heart and is also a heart- and muscle-specific miRNA. In a cardiac cell necrosis model induced by Triton X-100 in vitro, we found that cardiac miR-1 can be released into the culture medium and is stable at least for 24 h. In a rat model of AMI induced by coronary ligation, we found that serum miR-1 is quickly increased after AMI with a peak at 6 h, in which an increase in miR-1 of over 200-fold was demonstrated. The miR-1 level returned to basal levels at 3 days after AMI. Moreover, the serum miR-1 level in rats with AMI had a strong positive correlation with myocardial infarct size. To verify further the relationship between myocardial size and miR-1 level, an IP (ischaemic preconditioning) model was used. The results showed that IP significantly reduced circulating miR-1 levels and myocardial infract size induced by I/R (ischaemia/reperfusion) injury. Finally, the levels of circulating cell-free miR-1 were significantly increased in patients with AMI and had a positive correlation with serum CK-MB (creatine kinase-MB) levels. In conclusion, the results suggest that serum miR-1 could be a novel sensitive diagnostic biomarker for AMI.